Jovens e estratégias educativas de apropriação dos espaços urbano e virtual - Cavalcante, Cláudia Valente (2010)
Due to technological advance changes new spaces for sociability and formation are being set up in society, in particular, the cyberspace has extended new possibilities of interaction and communication as well as virtual societies are becoming more popular among youngsters. This work aims to understand how youngsters from different backgrounds deal with Jardim Novo Mundo Virtual Community and which educational and social strategies are being used in order to achieve digital and real life insertion. Based on Pierre Bourdieu references the world appreciation and perception varies according to the social position of the social agents, in which tastes and lifestyles are attached to their social space position, Strategy concept is used for analytical purposes and it refers to the agent capacity of taking action in different social fields along with ownership and maintenance of different types of capital. The main question is to know how these youngsters are taking advantage of the virtual community to raise both cultural and social capital. To what extend these strategies meet educational and social purposes? Aiming to answer this question a questionnaire, online and face to face interview and observation of a virtual community were used which have enabled apprehend the dynamics and socialcultural insertion forms of the young people and the social representations and practices of use of Internet. The Jardim Novo Mundo Virtual Community participants expose two different concepts of being young: a group perceives youth as time to enjoy life and the other group manifests the absence of such freedom. The school is perceived not only as a mobility factor, but also as a symbolic goods acquisition way. The school trajectory is discontinuous as their parents . Work is taken as an activity carried out for survival. Religion is an important issue for some youngsters as an upholder and spaces of sociability venues. For those out of school they tried to be connected to the socialcultural environment through Internet, therefore obtaining social and cultural capital through both individual or collective strategies. The Jardim Novo Mundo Community comprises the youngsters highlighted in this research and for them it is a resistance area to challenge negative media portrait. It is also a place for sociability, formation and work presentation. Summing up, youngsters access social networks at local lanhouses where collaborative learning is effective. The comprehension of youth relations, school, family, religion, work and social networks allows us to state that these young people build up their own educational strategies to take part in the sociocultural world.